Estimation of sensitiveness of the seismic station AIA on results of registration of signals from seismic sources - A. I. Liashchuk; V. Shapka; Yu. Gordienko; Ye. V. Kariagin (Ukrainian Antarctic Journal, 2006)
In the article the results of analysis of seismic background are represented at the Ukrainian Antarctic station the «Academic Vernadsky», the degree of his influence is certain on registration of useful seismic signals. The sensitiveness of the station is appraised to the regional and teleseismic events.